Synoptic-on the mediatization of Filipino youth-led civil society organizations’ demand for government accountability in Foucault’s Theory of Power - Sto. Tomas, Michelle Anne N.
Mediatization calls for a critical examination of the changes in communication and media, and culture and society. Mathiesen argues that contemporary society is shaped by the synopticon, where media empowers a ‘Viewer Society.’ Today, new media have become a marketplace of ideas where the public can discuss policies and express their criticisms of the government, suggesting progress on how civil society demands government accountability, where surveillance plays a key role. Inspired by a Foucauldian theory of power, I investigated the changing demand for government accountability among youth-led CSOs in the Philippines and argued that they create a remarkable influence by navigating the complexities of media logics today. I used a synchronous approach to mediatization research through digital ethnography to study this media wave. I observed 30 youth-led CSOs on their Facebook Pages segmented into batches. Each batch has five CSOs observed daily for 30 days, totaling 65 days of observation altogether. At least one CSO from a batch was probed through an interview. The findings reveal that the CSOs’ operations are unfinished in the fourth media wave, compelling them to abide by media logics. As the media themselves today, their counter-surveillance modus operandi is digital influence advocacy and journalism. In a Foucauldian modern synopticon, new media are tools of power for CSOs to insinuate to the government that they are being watched, imposing greater pressure for accountability. Findings reveal that a discursive approach can draw practical implications for how CSOs in political spaces can enact their agency. Ultimately, I presented criticisms of short-term digital ethnography and argued its congruence with mediatization research.